Quo Vadis Marriage Dispensation in Indonesia: Judge's Decision in Preventing Child Marriage at the Jepara Religious Court - Aristoni Aristoni (Fakultas Syariah, 2022)
This article aims to explore how to optimize the judges of the Jepara Religious Court in preventing child marriage amid increasing requests for dispensation every year as a result of changing the age limit for marriage in the Marriage Law. To answer these objectives, this article uses a type and research approach, namely sociological juridical with a qualitative basis. The primary data source was obtained directly from the informants, namely the Jepara Religious Court judges. The secondary data sources are in the form of books and journals which are still relevant to this theme. To obtain the data and information needed in this article, data collection techniques such as interviews were used. After the data is obtained, the next step is to process the data using data analysis techniques in the form of descriptive qualitative. The results of this study indicate that the optimization carried out by the judges of the Jepara Religious Court in preventing child marriage along with the increase in cases of requests for dispensation of marriage include carrying out administrative tightening and adding recommendation letters from doctors or midwives, and recommendation letters from social services or workers following Court Regulation Number 5 the Year 2019. In addition to conducting massive and simultaneous outreach by involving all elements of society such as religious leaders, community leaders, parents or guardians, families, educational institutions, NGOs, and local government to provide education to the public so they have legal awareness and provide an understanding of negative effects of child marriage.